Biased Volcanic Hazard Assessment Due to Incomplete Eruption Records on Ocean Islands: An Example of Sete Cidades Volcano, Azores - Kueppers, Ulrich; Pimentel, Adriano; Ellis, Ben; Forni, Francesca; Neukampf, Julia; Pacheco, José; Perugini, Diego; Queiroz, Gabriela (Frontiers in Earth Science, 2019)
Sete Cidades is the westernmost central volcano of São Miguel Island, Azores. Although currently dormant, it has been the most active volcano on the island in the past 5 ky, with at least 17 trachytic intra-caldera explosive eruptions, some of which of sub-Plinian. The last paroxysmal explosive eruption took place ~16 ka, enlarging the summit caldera to its present dimensions, and is recorded by the Santa Bárbara Formation. It is well known that explosive eruptions pose serious hazards to local communities and may have worldwide impacts. However, the products of explosive eruptions on volcanic islands are almost inevitably incompletely preserved, thereby impeding our ability to precisely determine eruptive source parameters. These constraints are frequently observed on volcanic ocean islands, such as the Azores islands, where it is estimated that a significant portion of the erupted material is deposited into the sea. We here present evidence of a distal deposit (>25 km from the vent) that can be correlated with the pumice fall deposit of the Santa Bárbara Formation based on deposit characteristics, textural features and geochemistry. This is the first evidence of a decimeter-thick distal deposit of Sete Cidades volcano in the central part of São Miguel Island, which allows to constrain eruptive source parameters and wind conditions. The predominant winds blowing from westerly directions makes Sete Cidades the most hazardous volcano for the entire island of São Miguel with its current population of >137,000 inhabitants. Most critically, the main harbor, only airport and hospital are located in the capital city of Ponta Delgada, ~12 km SE from Sete Cidades caldera. In case of a future explosive eruption, under westerly-blowing wind conditions, the impact on São Miguel will be catastrophic, with long-term economic consequences.